Persistent Polioviral Infection of Intact Human Amniotic Membrane Without Apparent Cytopathic Effect - Gresser, Ion (1965)
Gresser, Ion (Children's Hospital Medical Center, Boston, Mass.), Charles Chany, and John F. Enders. Persistent polioviral infection of intact human amniotic membrane without apparent cytopathic effect. J. Bacteriol. 89:470–475. 1965.—Poliovirus type I multiplied in organ cultures of the intact amniotic membrane. The behavior of the virus in this system differed markedly from that observed in monolayer cultures of trypsinized amnion cells, since replication of new virus was demonstrable throughout a period as long as 3 months, extensive cellular destruction was not apparent, and only a small proportion of cells were found to be infected at a given time. It seems likely that the chronicity of infection is conditioned essentially by the persistent insusceptibility to polioviral infection of the large majority of cells (relative to monolayer cultures) rather than to interferon, which was present in the culture fluids. It was postulated that the greater suceptibility of cultured amnion cells to infection, as compared with cells of the intact membrane, is due in part to the enhancement of phagocytic activity attendant upon trypsinization and cultivation of the amnion cells in monolayers. Amniotic and chorionic membranes thoroughly washed free from blood contain and release in vitro antibody to poliovirus I and other viruses. Appreciation of this phenomen may be important in attempts to isolate viruses from infected tissues.